Властивості наноструктур із плазмонними резонансами - Мартинюк, Є. Д. (ХНУРЕ, 2022)
The paper considers an urgent scientific problem of effective numericalanalytical study of stationary fields in a metal nanowire. To solve the problem, a rigorous mathematical approach was used, which made it possible to identify all possible configuration plasmons without any restrictions on the transverse size. This approach guaranteed obtaining results with controlled accuracy, ease of interpretation of phenomena, and created a complete physical picture of the nonstationary processes that are observed in such a structure.
Keywords: наноструктура; плазмонний резонанс; біосенсор